Plasmon Enhanced Spectroscopy of N,N′-Dialkylquinacridones Used as Codopants in OLEDs - del Puerto, Elena; Domingo, Concepción; Sanchez-Cortes, Santiago; García-Ramos, Jose V; Aroca, Ricardo F (Journal of physical chemistry. C, 2011)
Plasmon-enhanced Raman scattering and plasmon-enhanced fluorescence of the two molecules N,N′-dimethylquinacridone (DMQA) and N,N′-diisoamylquinacridone (DIQA) used as codopants in OLEDs (with improved stability) are reported. The work includes a complete vibrational characterization using Raman and infrared spectra supported by DFT calculations. Plasmon enhancement is achieved using silver and mixed Ag/Au nanostructures: colloids and metal island films, supporting localized surface plasmon resonances (LSPR). However, fine-tuning of the experimental conditions is necessary to attain surface-enhanced (resonance) Raman scattering (SERS/SERRS) of the two molecules with similar structures. SERRS spectra of DMQA are obtained on silver colloids and from a Langmuir–Blodgett (LB) monolayer deposited onto silver island films (SIF). High quality SERRS spectra of DIQA were only obtained from LB layers on mixed Ag/Au island films. Using spacer LB layers of arachidic acid (AA) to separate the fluorophore from the metal nanostructure, surface-enhanced fluorescence (SEF) spectra for both quinacridones were obtained on silver island films. The spectral data provided information on the subject of the molecular aggregation in the LB layers.